Humanistic Approach in Islamic Education: Building Emotional and Spiritual Intelligence in the Digital Age - Zaenal Abidin; Ahmed Mahfooz; Fauziah Sulaiman; Hairul Fauzi (Zabags International Journal of Islamic Studies, 2024)
This study examines the application of the humanistic approach in Islamic education in the digital era, with a focus on the development of students' emotional and spiritual intelligence. Amidst rapid technological advances, there is a risk that emotional and spiritual aspects are often neglected in the learning process. The humanistic approach is considered a solution to maintain a balance between cognitive mastery and character development. Through a literature review, this study found that the humanistic approach can strengthen interpersonal relationships, support moral and spiritual development, and provide a framework for more meaningful technology integration. The conclusion of this study is that the integration of humanistic principles in Islamic education is not only relevant but also essential to forming holistic and balanced individuals in the digital era. It is recommended that Islamic education integrates the humanistic approach with technology to support the development of students' emotional and spiritual intelligence holistically in the digital era. The study concludes that in order to create well-rounded, well-balanced people in the digital age, humanistic concepts must be incorporated into Islamic education. This integration is significant and necessary. To help students develop their emotional and spiritual intelligence holistically in the digital age, it is advised that Islamic education incorporates technology and the humanistic approach